2010
DOI: 10.1093/gerona/glq002
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone-Binding Globulin as an Independent Predictor of Incident Type 2 Diabetes Mellitus in Men

Abstract: SHBG is an independent predictor of incident T2DM even after adjusting for free T or total T. Free T is not significantly associated with T2DM. SHBG may contribute to the risk of T2DM through nonandrogenic mechanisms, which should be investigated as they may provide novel targets for diabetes prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 53 publications
(44 reference statements)
7
84
5
2
Order By: Relevance
“…The observed associations were only partially attributable to obesity and insulin resistance [43,44]. Similar prospective studies have also been performed in men, yielding essentially the same results: decreased SHBG levels are associated with higher risks for T2DM e even after adjusting for known risk factors and for total and free T [45,46]. In good agreement with these studies, a nested caseecontrol study in men and postmenopausal women demonstrated that in both sexes low SHBG levels predict development of T2DM [47].…”
Section: Shbg and Its Association With Metabolic Syndrome And Type 2 supporting
confidence: 70%
“…The observed associations were only partially attributable to obesity and insulin resistance [43,44]. Similar prospective studies have also been performed in men, yielding essentially the same results: decreased SHBG levels are associated with higher risks for T2DM e even after adjusting for known risk factors and for total and free T [45,46]. In good agreement with these studies, a nested caseecontrol study in men and postmenopausal women demonstrated that in both sexes low SHBG levels predict development of T2DM [47].…”
Section: Shbg and Its Association With Metabolic Syndrome And Type 2 supporting
confidence: 70%
“…Despite some studies 17 suggesting that middle-aged patients with type 2 diabetes usually present lower levels of testosterone, a recent prospective study showed that free testosterone was not associated with type 2 diabetes and that SHBG may contribute to the risk of type 2 diabetes, through non-androgenic mechanisms. 18 Various authors have investigated the relationship between AGA and cardiovascular involvement, such as hypertension 19,20 or dyslipidaemia. 8 In addition, hyperglycemia and diabetes can be associated with AGA as we show in this case-control study and may contribute to higher frequency of metabolic syndrome and carotid atheromatosis found in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different components of HPT function may 'age' differently and/or respond differentially to health and lifestyle modifications. The age-related increase in sex hormone-binding globulin (SHBG) (17), and its fluctuation in response to changes in metabolic status, can influence bioavailability of testosterone and contribute to alterations in HPT axis function (18,19,20,21,22).…”
Section: Introductionmentioning
confidence: 99%